Analisis Beban Kerja Mental Mahasiswa saat Perkuliahan Online Synchronous dan Asynchronous Menggunakan Metode Rating Scale Mental Effort - Fatin Saffanah Didin; Intan Mardiono; Hersa Dwi Yanuarso (OPSI, 2020)
In 2020, Indonesia experienced a pandemic known as the Corona Virus or Covid-19. The government-imposed social distancing rules affect Indonesian society for teaching and learning activities at the university. Governments impose rules on online learning systems. The online learning system provides convenience, but on the other hand, there are adverse impacts for some students, one of which has a mental workload. The study aims to measure and analyze student mental workloads using the Rating Scale Mental Effort (RSME) method. The number of respondents was 111 students. The mental workload measured is a quantitative learning system that is quantitative with the delivery of the material directly (Synchronous) and the delivery of the material using the recorded video in advance (Asynchronous). The indicators of mental work effort are workload, work difficulties, job satisfaction, mental effort, anxiety, and work fatigue. The measurement results show that the RSME value of the workload indicator and the work difficulties between the online learning methods are significantly different. Mental workloads, technical difficulties, work mental ventures, work anxieties and work fatigue when online learning is high enough on the learning system using Synchronous, with a value of 93.27; 94.5; 94.27; and 96.54. However, for job satisfaction, students are more satisfied learning by using video recording than Synchronous, i.e., several 79.61. The results show that the recommended online learning method is with video recording.